Analysis of demand and supply in the Colombian housing market: impacts and influences 2005-2016. Issue 1 (10th January 2018) - Vargas Walteros, Camilo; Novoa Hoyos, Amalia; Arias Ardila, Albert Dario; Peña Ballesteros, Arnold Steven
Abstract : Purpose: The purpose of this paper is to provide an estimate of the demand and supply in the housing market in Colombia in a period of high real estate valuation (2005-2016). On the demand side, it evaluates the impact of new housing prices, unemployment, stock market returns, real wages in the retail sector, remittances and mortgage rates. On the supply side, it estimates the influence of the price of new housing, construction costs, time deposit (TD) and mortgage rates. Real estate valuation was analyzed considering foreigners migration and land prices evolution. Design/methodology/approach: Ordinary least squares (OLS) was used to estimate housing area with the semilog regression model and also to construct price models. OLS was also used in price models. Since quantities depend on prices and vice versa, a two-stage least squares (2SLS) was implemented. Findings: Rising prices in new homes have an "elastic" effect on both demand and even higher effect on supply. Likewise, the real wage index for the retail sector has an elastic effect. On the other hand, the response to interest rates is negative, but statistically significant only on the supply side. Furthermore, the inflow of remittances is "inelastic" and statistically insignificant. Originality/value: Housing can sometimes be a Giffen good, this result challenges the traditional neoclassical model, but it can be explained by investment reasons and "bubble" behavior in the housing market. One last influence is the difference between "temporary" and "permanent" migrations. The latter has a statistically significant and perfectly inelastic effect on the price of new homes.